2012
DOI: 10.1038/hr.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity modifies the association between CYBA gene polymorphisms and small artery elasticity in a Chinese population

Abstract: Emerging evidence suggests that increased superoxide production is responsible for a significant proportion of endothelial dysfunction. The relationship between variants of the CYBA gene and cardiovascular diseases is currently debated. In the present study, we investigated the influence of CYBA polymorphisms (rs1049255 and rs7195830) on arterial elasticity in a Chinese population. In the 2178 participants enrolled in the GaoYou study, we measured large artery elasticity (C1) and small artery elasticity (C2) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The protocol was approved by the Ethics Committee of the First Affiliated Hospital with Nanjing Medical University. Informed consent was obtained and signed by each participant [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol was approved by the Ethics Committee of the First Affiliated Hospital with Nanjing Medical University. Informed consent was obtained and signed by each participant [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Stepwise logistic regression analyses were used to evaluate the factors that were independently associated with OA in the whole population, and separately in women and men; P -values for covariates to be included in the model were set at 0.05. P -values < 0.05 were considered statistically significant, and all tests were two-tailed [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The method of study population enrollment has been published previously[10],[11]. Briefly, stratified random sampling was used to select a representative sample from the towns of Baqiao and Songqiao in Gaoyou, a city 170 km north of Nanjing, China.…”
Section: Methodsmentioning
confidence: 99%
“…The waist-to-hip ratio was calculated using the smallest circumference at the waist divided by the largest circumference at the hip. For detailed information, refer to our previous study[10],[11].…”
Section: Methodsmentioning
confidence: 99%
“…Further researches will be needed to confirm our hypothesis, and the important effects of other confounding factors should also be studied. It has been reported that physical activity could modify this genetic effect of the CYBA gene (Zhu et al, 2012). 640A>G polymorphism in the CYBA gene have also been implicated in the development of cardiovascular disease (Goliasch et al, 2011;Xu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%